Effective Business Management Strategies and Their Application in Mitigating the Risks of Real Estate Development Projects in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
The research intends to investigate efficient business management methods and their application in minimizing risks associated to real estate development projects in the Kingdom of Saudi Arabia. The questionnaires were delivered to a sample of 163 participants working in sectors connected to the study topic, and the data was examined using statistical analysis, which confirmed the reliability of the responses and the correctness of the findings. The findings highlight the essential significance that competent management methods play in decreasing the financial risks connected with real estate development projects. By implementing effective management practices, financial risks coming from market volatility, project delays, or cost overruns may be mitigated. The findings also revealed the need of good management methods in activating sustainable practices within these projects, since this contributes to the viability of projects in the long run by caring for the environment and resources. In addition, good management methods play a vital role in promoting transparency within real estate development projects, as they assist explain financial and administrative procedures, which adds to developing confidence among all parties engaged in the project. In conclusion, the research indicated that competent management is not only a tool for lowering risks, but also a vital aspect in assuring the sustainability and transparency of real estate developments in the Kingdom.
Keywords: Business Management Strategies; Project Risks; Real Estate Development Projects